Strategi Komunikasi Interpersonal Kepala Desa dalam Mensosialisasikan Bantuan Sosial kepada Masyarakat di Tengah Pandemi Covid-19 di Desa Pinanggripan - Damanik, Mita Anggraini; Harahap , Suheri; Devianty, Rina (Medan Resource Center, 2022)
This article aims to discuss the village head's interpersonal communication strategy in disseminating social assistance to the community amid the Covid-19 pandemic in Pinanggripan Village. The theories used in this research are social penetration theory, communication planning theory, and leadership theory. This research is a type of descriptive qualitative research. There are three data collections in this study, namely observation, in-depth interviews and documentation. The research results were obtained from 5 informants consisting of the village head and 4 people from the village of Pinanggripan. From the results of the study it can be concluded that the village head's interpersonal communication strategy in socializing social assistance to the community in the midst of the co-19 pandemic in Pinanggripan was successful. The existence of social assistance provided to the Pinangripan community in the midst of the Covid-19 pandemic has helped the community meet their needs when the pandemic occurred.